Komunikasi Partisipatif Masyarakat Kota Depok dalam Penyebaran Informasi Program Bank Minyak Jelantah - Kosasi, Meillano Dimas; Riyantini, Rini; Damayanti, Damayanti (Jurnal Pustaka Komunikasi, 2025)
Used cooking oil is the result of the cooking process of fried food. If this used cooking oil is used more than once for frying, the oil will oxidize and produce compounds that are harmful to the human body. The Used Cooking Oil Bank program initiated by the Depok City Government is an environmental initiative that aims to educate and invite the public to manage used cooking oil waste wisely and sustainably. To support the success of this program, a participatory communication approach is the main strategy in disseminating information and inviting active community involvement. In Depok City, the implementation of participatory communication in the Used Cooking Oil Bank program is carried out through various stages designed to create a sense of ownership of the program. Researchers used a qualitative approach in this study with a case study method. Data collection methods include observation and interviews. The results of the study showed that the success of information dissemination by the community was also supported by the existence of an incentive and reward system, both in the form of material and social recognition. Several communities provide rewards or appreciation to residents who actively deposit used cooking oil regularly.